Exchange rate coordination in Asia: Evidence using the Asian Currency Unit - Abhijit Sen Gupta (Asian Development Bank Institute (ADBI), 2012)
This paper evaluates the extent of exchange rate coordination among Asian economies using a hypothetical Asian Currency Unit. Rising interdependence among Asian economies makes it vital for these economies to have a certain degree of exchange rate stability. However, the empirical evidence using an Asian Currency Unit suggests a widening deviation in exchange rate movements of the Asian currencies. The deviation has been driven by the adoption of different exchange rate regimes by the participating countries indicating diverse policy objectives. There are a number of institutions in the region that can assist exchange rate coordination and greater economic and financial integration. These institutions, including a multilateralized swap arrangement, a regional surveillance mechanism, and a bond fund; have to be significantly strengthened for them to play a role in fostering greater economic cooperation. The denomination of financial assets in the Asian Currency Unit in transactions involving these institutions would also enhance exchange rate cooperation.
Keywords: F36; F55; F15; 330; exchange rate coordination; asia; asian currency unit; exchange rate regimes; Währungskorb; Wechselkurspolitik; Internationale Wirtschaftspolitik; Währungsrisiko; Wechselkurssystem; Asien